The Influence of Information and Communication Technology and Demographic Variables on the Indonesian Economy: Before and During COVID-19 - Ferayanti, Ferayanti; Varlitya, Cut Risya; Sitepu, Novi Indriyani; Seftarita, Chenny (Graha Primera Saintifika, 2025)
Changes in population and advancements in information and communication technology (ICT) have significantly transformed the global economy. While the individual effects of these factors on economic growth have been extensively studied, little is known about their interaction, particularly in the context of the COVID-19 pandemic. The pandemic introduced new economic dynamics by altering consumer behavior and accelerating the adoption of digital technology. This study investigates the combined impact of ICT advancements and demographic shifts on Indonesia's economic growth before and after the pandemic. Using panel data from 2015 to 2021, a regression model explores the correlations between these factors. The results reveal that e-commerce, internet usage, and demographic factors positively influence economic growth. However, a negative correlation is observed between economic growth and mobile phone usage. Notably, economic expansion driven by ICT was more pronounced in the pre-COVID-19 period than in the post-pandemic era. To fully harness the potential of digital transformation and sustain growth, government interventions are essential. These include supporting MSMEs in developing digital capabilities, accelerating digital infrastructure development, enhancing digital human resources, streamlining regulations, and leveraging big data to guide policy decisions.